2017
DOI: 10.3390/antibiotics6040023
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Patient Awareness and Perceptions of the Appropriate Use of Antibiotics: A Mixed-Methods Study

Abstract: In the outpatient setting, estimates suggest that 30% of the antibiotics prescribed are unnecessary. This study explores patient knowledge and awareness of appropriate use of antibiotics and expectations regarding how antibiotics are used for their treatment in outpatient settings. A survey was administered to a convenience sample of patients, parents, and caregivers (n = 190) at seven primary care clinics and two urgent care locations. Fisher’s exact tests compared results by patient characteristics. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 17 publications
6
62
0
Order By: Relevance
“…This finding is comparable to previous studies in Malaysia, whereby more than 80% of adult respondents in Putrajaya [37] and Penang [35], and elderly respondents in Cheras [28] also failed to identify that antibiotics do not eradicate viral infections. The finding of the misconception that antibiotics work on both bacterial and viral infections was not uncommon in other studies in the world [26,30,31,38,43,45,48,57,58], because the general public incorrectly believed that antibiotics can speed up the recovery from most cough and cold [21,24,30,45,48,52]. In addition, more than half of the respondents in this study were not able to differentiate antibiotics from other commonly used medications such as analgesics and antipyretics, similar to that reported in Penang (69.1%) [35].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This finding is comparable to previous studies in Malaysia, whereby more than 80% of adult respondents in Putrajaya [37] and Penang [35], and elderly respondents in Cheras [28] also failed to identify that antibiotics do not eradicate viral infections. The finding of the misconception that antibiotics work on both bacterial and viral infections was not uncommon in other studies in the world [26,30,31,38,43,45,48,57,58], because the general public incorrectly believed that antibiotics can speed up the recovery from most cough and cold [21,24,30,45,48,52]. In addition, more than half of the respondents in this study were not able to differentiate antibiotics from other commonly used medications such as analgesics and antipyretics, similar to that reported in Penang (69.1%) [35].…”
Section: Discussionmentioning
confidence: 85%
“…Previous work has discussed the benefits of using the specific terms "bacteria" and "virus" when providing medical consultations to patients [57]. In addition, frequent prescribing of antibiotics in viral infections and inconsistency in antibiotic prescribing by different prescribers for the same symptoms might have caused confusion to older adults [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings regarding limited public understanding about the potential harms of antibiotic overuse are reflected in other studies, which suggest that patients may lack awareness and/or may not view this issue as personally relevant . Furthermore, two systematic reviews of interventions aimed at reducing antibiotic prescriptions for children with respiratory tract infections found that the most effective interventions simultaneously target parents and clinicians .…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, these results collectively suggest that participants see roles for patients, physicians, and the government in addressing an- Our findings regarding limited public understanding about the potential harms of antibiotic overuse are reflected in other studies, which suggest that patients may lack awareness and/or may not view this issue as personally relevant. 13,14,33,44…”
Section: Key Themes and Tensions Description And Subthemes Example Qumentioning
confidence: 99%